Pieces Analysis to Improve Performance Cash Sales System: A Case Study on The Darmo Deli Supermarket - anisa fitri syabania (Universitas Airlangga, 2022)
Darmo Deli Supermarket is a growing retail company. Cash sales is the main source income for that company. In order to improve its performance, it is deemed necessary to conduct an analysis of the cash sales system at the Darmo Deli supermarket. A qualitative approach with observation, interviews, and documentation was used to obtain information about the cash sales flow and system that had been implemented. PIECES analysis has 6 aspects, performance, information, economic, control, efficiency and service. The results of the study show that the Darmo Deli Supermarket cash sales accounting information system has no warehouse section. Based on PIECES analysis, the control aspect of the cash sales system needs to be improved. So that, the fraudulent sales data reporting can be avoided, velocity and accuracy of financial reports in Darmo Deli Supermarket cash sales system can enhanced.